Investigating the Antifungal Effects of Mineral Trioxide Aggregate and Indigenously Developed Bioceramic Cement Ceremagnum Plus on Candida Albicans by Invitro Evaluation - Dr. Anusua Mitra, Dr. Sonali Sharma (South Eastern European Journal of Public Health, 2025)
The aim of this in vitro study was to evaluate the antifungal efficacy and to determine the minimal inhibition concentration (MIC) of MTA and indigenously developed Ceremagnum plus against Candida albicans. Sabouraud dextrose agar plates containing various concentrations of MTA powder, Ca(OH)2 and indigenously developed Ceremagnum plus were prepared. The plates were inoculated with an overnight culture of C. albicans, then observed for the formation of colonies after incubation at 37 °C for 24. The minimal concentration at which inhibition of the microorganism occurred was measured and noted as the MIC. There was a statistically significant difference in the antifungal effect between the concentrations of 50mg /ml,25mg/ml,12.5mg/ml,6.25mg/ml,3.12mg/ml,1.56mg/ml,0.78mg/ml,0.39mg/ml,0.19mg/ml and 0.009mg /ml. The MIC of MTA, Ca (OH)2 and indigenously developed Ceremagnum plus against C. albicans.